Studi Awal Upaya Eksplorasi Agensia Imunokontrasepsi Untuk Regulasi Fertilitas Hewan Liar : Pofil Protein Selama Proses Implantasi Embrio Mencit (Mus musculus L.) BALB/c. - Sitasiwi, Agung Janika; Djaelani, Muhammad Anwar (Bioma : Berkala Ilmiah Biologi, 2011)
Study on exploration of immunocontraception agents for wildlife fertility regulation has been conducted.The aim of this study was carried to find out the protein which functionable in mice embryos implantation. Theoutcome of this study should be applied to control the fertility of wildlife animals. This research conducted duringten months in BSF Laboratory of Biology Department FMIPA UNDIP and 3rd Unit of UGM LPPT. Adult femaleand male mice with 28 – 30 grams in weight were used as laboratory animals. Mice were divide into two groups, onegroup as positive control group without mated, the other were mated group. Mice handled and breeded in laboratorycondition. The precise day of pregnancy were determined with vaginal plug existences in female mice. Protein wereisolated from uterus on day 1st to 5th of pregnancy. Protein isolation and separation with electrophoresis were basedon Bio-rad manual. This study show that there are no differences in protein band between positive control group andpregnant group. These study suggested that protein determining embryo implantation process is regulatory proteinwhich it has expressed in short time and fast withdrawl.